The Impossibility of a Critically Objective Criminal Law - Baker, Dennis (McGill Law Journal / Revue de droit de McGill, 2011)
In this paper, I argue that principled criminalization does not have to rely on critical objectivity. It is not necessary to demonstrate that conduct is criminalizable only if it is wrong in a transcultural and truly correct sense. I argue that such standards are impossible to identify and that a sounder basis for criminalization decisions can be found by drawing on our deep conventional understandings of wrong. I argue that Feinberg’s harm principle can be supported with conventional accounts of harm, and that such harms can be identified as objectively harmful when measured against our deep conventional understandings of harm. The distinction that critical moralists make between truly harmful conduct and conventionally objective harmful conduct is unsustainable because many conventional harms impact real victims in social contexts. The best that we can do is to scrutinize our conventional conceptualizations of harm and badness, but that scrutiny is constrained by the limits of epistemological inquiry and our capacity for rationality at any given point in time. Many acts are criminalizable because they violate social conventions that are shareable by communally situated agents.